THE RELATIONSHIP BETWEEN NUMERICAL ABILITY, PARENTAL ATTENTION, AND DISCIPLINE OF LEARNING WITH STUDENTS MATHEMATICS LEARNING OUTCOMES IN CLASS VII - Ifan Arifin; Widayati Widayati (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2018)
Based on the observation in SMP Muhammadiyah 9 Yogyakarta obtained some information that low numerical ability, parents pay less attention to children/students in terms of learning, and student learning discipline is less. This study aims to determine whether or not a positive and significant relationship between numerical ability, parental attention, and discipline of learning with the results of learning mathematics seventh-grade students  Muhammadiyah Junior High School 9 Yogyakarta (SMP Muhammadiyah 9 Yogyakarta) even semester 2016/2017 academic year. SMP Muhammadiyah 9 Yogyakarta academic year 2016/2017 consists of 5 classes. All classes have an average value of final exams that is almost the same, so that the population in this study is class seventh gradee A to seventh grade E. Sampling technique using random sampling technique to class and class of VIIC selected as sample class. Data collection techniques used questionnaires and tests. The data collection instrument uses numerical ability tests, questionnaires of parental attention, discipline study questionnaires, and learning results. Test of research instrument using validity test, reliability test, and different power tests. The prerequisite analysis test includes a normality test, linearity test, and independence test—data analysis for hypothesis testing using product-moment correlation analysis and multiple linear regression analysis.  The results showed a positive and significant relationship between numerical ability, parental attention, and discipline of learning with the results of learning mathematics. At a significant level of 5%, v1 = 3, v2 = 28, Fcount = 49,9147137 and Ftable = 2,946685269, Fcount> Ftable with double correlation coefficient R = 0.917861751 and multiple regression equation three variables namely Y = -18 , 86970257 +0,385695364 X1 + 0,260272591 X 2 + 0,599196062 X3. Relative contribution X1 = 38,54162209%, X2 = 48,612,2907%,  X3 = 48,612,2907%, with double determination coefficient 0,842470194 and effective contribution X1 = 32,47016786%, X2 = 10,8224975% and X3 = 40,95435408%.